Listening space: Lessons from artists with and without learning disabilities. (April 2016) - Macpherson, Hannah; Fox, Alice; Street, Susan; Cull, John; Jenner, Tina; Lake, Des; Lake, Martyn; Hart, Shirley
In this paper, we develop an expanded conception of listening as 'being-with' and explore this in the context of creative visual arts activities with people with learning disabilities. Through a series of textual and visual interlocutions between Inclusive Artist 'Alice', Social and Cultural Geographer 'Hannah' and members of the contemporary arts group 'The Rockets', we identify how an expanded conception of listening is practiced and the results it produce. Where listening for the Inclusive Artist includes an attentiveness to visual, verbal and gestural vocabularies of arts-based methods; the construction of conducive spaces for listening and voice with attuned collaborators and appropriate art materials; the use of art materials as 'meeting points', which enable a non-verbal conversation to take place and knowledge of how particular materials and practices can influence a person's work and sense of themselves. The temporalities of these forms of expanded, attentive, curious listening are explored and concern is expressed about how they sit in opposition to the hasty demands for research with 'impact'. We hope this paper provokes researchers to consider what it means to listen through arts-based methods, the crucial role of the facilitator and the temporalities of listening they are bringing into being.